ANALISIS KINERJA KEUANGAN KABUPATEN/KOTA DI PROVINSI SULAWESI SELATAN - Mustafa Hasbar (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2010)
Performance Finance area of regency and town in to South arch Sulawesi, measured with the storey;level of effectiveness and independence start the year 2005-2007. From 23 regency/town, pursuant to result analyse known by some regency which less be effective even at category is not effective or with the Monetary Ratio Efektifitas (EKD) gyrate from in > 60 - 79,21 % and enter in very low finance independence category (ratio KKD 1% up to 25%) and also enter in category of pattern of relation instruktif, namely role of central government more dominant than local government independence.